TIMING OF ORTHODONTIC TREATMENT OF MALOCCLUSIONS IN THE MIXED DENTITION PERIOD - Maria Alexandra Martu (Romanian Journal of Medical and Dental Education, 2019)
The ideal time to initiate orthodontic treatment in children is a controversial subject in the scientific literature. Beginning treatment in the, even though tempting, has a disadvantage in the fact that recommended wrongfully can prolong treatment, sometimes spanning to up to 10 years and leading to patient burnout and dissatisfaction. However, waiting until the late mixed dentition also has its disadvantages. Commencing treatment in the permanent dentition implies compliance issues with teenage patients, female patients with little growth remaining. Early mixed dentition treatment often focuses on skeletal rather than dental correction. In order to design a comprehensive treatment plan, the clinician must have a complete grasp of the growth and development patterns, but also of the outcome of the chosen treatment option. Is there a conclusive benefit of early treatment for certain orthodontic issues? This question has yet to be fully answered by researchers. The clinician can diagnose and intercept certain developing problems with early treatment. Many other cases on the other hand should be supervised, but not treated until the permanent teeth are erupted.